Tillagning i mikrovågsugn och dess effekt på livsmedel : en jämförelse med konventionell tillagning - Gottfridsson, Linda (SLU/Dept. of Food Science, 2011)
Microwave is a time- efficient device for heating and reheating of foods. Despite the fact that its effects on foods have been evaluated during a long period of time, without any more negative effects shown compared to conventional cooking, one third of the Swedish population believes (in 2010) it accounts for a higher loss of nutrition.